An Overview of Tissue-Resident Memory T Cells in the Intestine: From Physiological Functions to Pathological Mechanisms - Lyu, Yangbao; Zhou, Yuming; Shen, Jun (Frontiers in Immunology, 2022)
The human intestine contains a complex network of innate and adaptive immune cells that provide protective immunity. The dysfunction of this network may cause various chronic diseases. A large number of T cells in the human intestine have been identified as tissue-resident memory T cells (TRM). TRM are present in the peripheral tissues, and they do not recirculate through the blood. It is known that TRM provide rapid immune responses at the frontline of pathogen invasion. Recent evidence also suggests that these cells play a role in tumor surveillance and the pathogenesis of autoimmune diseases. In this review, we discussed the general features of intestinal TRM together with their role in intestinal infection, colorectal cancer (CRC), and inflammatory bowel disease (IBD).